Cellular Composition of the Preoptic Area Regulating Sleep, Parental, and Sexual Behavior - Tsuneoka, Yousuke; Funato, Hiromasa (Frontiers in Neuroscience, 2021)
The preoptic area (POA) has long been recognized as a sleep center, first proposed by von Economo. The POA, especially the medial POA (MPOA), is also involved in the regulation of various innate functions such as sexual and parental behaviors. Consistent with its many roles, the MPOA is composed of subregions that are identified by different gene and protein expressions. This review addresses the current understanding of the molecular and cellular architecture of POA neurons in relation to sleep and reproductive behavior. Optogenetic and pharmacogenetic studies have revealed a diverse group of neurons within the POA that exhibit different neural activity patterns depending on vigilance states and whose activity can enhance or suppress wake, NREM sleep, or REM sleep. These sleep-regulating neurons are not restricted to the ventrolateral POA (VLPO) region but are widespread in the lateral MPOA and LPOA as well. Neurons expressing galanin also express gonadal steroid receptors and regulate motivational aspects of reproductive behaviors. Moxd1, a novel marker of sexually dimorphic nuclei, visualizes the sexually dimorphic nuclei of the POA (SDN-POA). The role of the POA in sleep and other innate behaviors has been addressed separately, more integrated observation will be necessary to obtain physiologically relevant insight that penetrates the different dimensions of animal behavior.